Navigating USFDA Inspectional Observations: An Analysis of Trends and Compliance from Fiscal Years 2019 To 2022 - Johnson, Antony Sebastian; Veeranna, Balamuralidhara; Maanvizhi, Saba (Indian Journal of Pharmaceutical Education and Research, 2025)
The Food and Drug Administration (FDA) known for its rigorous regulatory oversight, conducts routine inspections in the pharmaceutical industry, utilizing Form 483 to highlight observed non-compliances. Inadvertent breaches of intricate FDA criteria can lead to unsuitable conditions. Substantial violations triggering the issuance of Warning Letters (WL) serve as official notifications of federal law non-compliance, necessitating timely and effective responses to avoid severe consequences such as import denial, refusal, memoranda, or legal actions. Adherence to FDA’s regulations is imperative for ensuring product quality and public safety and navigating the complex landscape of pharmaceutical compliance. The study delves into cumulative trends in FDA inspection citations related to Good Manufacturing Practices (GMP) from FY2019 to FY2022 and the impact of the COVID-19 pandemic on FDA’s inspection process on drug manufacturers. Understanding the evolving GMP compliance landscape is crucial for industry stakeholders, given the FDA's continuous refinement of inspection protocols to ensure pharmaceutical product quality and safety. The analysis comprehensively examines the top GMP-related citations during the specified timeframe, identifying recurring themes and patterns. This research provides insights into the regulatory landscape, potential areas of industry improvement and emerging challenges faced by pharmaceutical manufacturers. In conclusion, this abstract emphasizes continuous monitoring, adaptation to evolving regulatory standards and a nuanced understanding of cumulative GMP citation trends. Upholding compliance, enhancing product quality and contributing to public health and safety remain paramount objectives in the dynamic regulatory environment of the pharmaceutical industry.
Keywords: Code of Federal Regulations-CFR; Fiscal Year-FY; Form 483 observation; Inspection; protocol; Regulatory oversight